True grit (2010) [videorecording (DVD)] - Coen, Ethan; Coen, Ethan; Coen, Ethan; Coen, Joel; Coen, Joel; Coen, Joel; Bridges, Jeff, 1949-; Damon, Matt; Brolin, Josh; Pepper, Barry, 1970-; Steinfeld, Hailee; Portis, Charles (Paramount Pictures, 2011)
Mattie Ross is determined to avenge her father's blood by capturing Tom Chaney, the man who shot and killed him for two pieces of gold. Just fourteen, she enlists the help of Rooster Cogburn, a one-eyed, trigger-happy U.S. Marshal with an affinity for drinking, and hardened Texas Ranger LaBoeuf to track the fleeing Chaney. Despite their differences, their ruthless determination leads them on a perilous adventure that can only have one outcome: retribution. Special features include featurettes.